Accelerated tree mortality after a half-century of stability in an old-growth forest: Insights from a 72-year study - Daniel C. Donato; Jerry F. Franklin; John L. Campbell; James A. Freund; Mark E. Harmon; Brian J. Harvey; Andrew J. Larson; James A. Lutz; Mark E. Swanson (Forest Ecology and Management, 2026)

Benchmarking and calibrating FVS diameter growth predictions with tree-rings and forest inventory data in Sierra Nevada mixed-conifer forests - Eugenia K.L. Batista; Joseph D. Birch; Matthew Dickinson; Chad M. Hoffman; James A. Lutz; Andrew J. Larson; Jessica R. Miesel (Forest Ecology and Management, 2026)

Accelerated erosion and tree mortality in a primeval temperate forest dominated by large trees, Washington, USA - Pavel Šamonil; Jakub Jaroš; Markus Egli; Nikola Polášková; Martin Hvězda; Dmitry Tikhomirov; Philip Gautschi; Mark E. Swanson; Andrew J. Larson; James A. Lutz (Geomorphology, 2026)

Drought conditioning influences conifer seedling height but not survival three growing seasons after planting - Anna C. Ross; Jeremiah R. Pinto; Justin S. Crotteau; David L.R. Affleck; Andrew J. Larson (Forest Ecology and Management, 2026)

Lake sturgeon ( Acipenser fulvescens ) growth and longevity estimated from adult capture–mark–recapture data - Edward A. Baker; Scott F. Colborne; Nancy A. Auer; Kim T. Scribner; Douglas L. Larson; Andrew S. Briggs; Ronald M. Bruch; Margaret H. Stadig; Michael C. Donofrio (Journal of Fish Biology, 2026)
Effective fishery management policy depends on accurate life‐history data, particularly for harvested species. Longevity is a core life‐history trait that is directly related to annual survival and lifetime reproductive potential, but fish longevity is generally not well documented, particularly for long‐lived species. We used capture–mark–recapture data spanning 44 years as an alternative method to estimate sex‐specific adult lake sturgeon ( Acipenser fulvescens ) average annual growth and longevity for five populations in the Laurentian Great Lakes. We determined individual fish average annual growth and fit population and sex‐specific exponential lines for average annual growth as a function of fish length at initial capture. We used the exponential equations to estimate age for 180 cm fork length (FL) female and 160 cm FL male lake sturgeon from each population by sequential subtraction of annual growth increments and assuming age at onset of sexual maturity of 24 and 15 years for females and males, respectively. Average annual growth estimates varied between sexes and among populations and ranged from 0.26 to 1.15 cm year −1 . Estimated ages also varied among populations. Age estimated for a 160 cm FL male lake sturgeon across the five populations ranged from 90 to 279 years. Age for a 180 cm FL female across populations ranged from 99 to 427 years. Our data suggest lake sturgeons live much longer than currently believed. High longevity and inferentially higher adult survival have important implications for sturgeons in general and support conservative harvest regulations for lake sturgeon fisheries.

Molecular relatedness-based analyses reveal breeding site philopatry in female bluntnose sixgill sharks (Hexanchus griseus) - Shawn Larson; Dayv Lowry; Kelly Andrews; Claude Dykstra; Francis Juanes; Brian Timmer; Samuel May (Frontiers in Marine Science, 2026)
The bluntnose sixgill shark ( Hexanchus griseus ) is a deep-water, globally distributed, but data-limited species due to its habitat use and cryptic nature. Its slow growth, long lifespan, and uncertain population status have prompted concern about its vulnerability and resulted in an IUCN Red List status of “Near Threatened.” A lack of information about critical habitat use throughout the species’ life cycle, such as breeding grounds, complicates direct management of the species. This study investigates the genetic diversity, population structure, relatedness, and reproductive behaviors of sixgill sharks in the Salish Sea, an inland fjord encompassing Washington State, USA and British Columbia Canada, one of the few known pupping and rearing grounds of the species globally. Using genomic sequencing of 274 tissue samples opportunistically collected over a 16-year timespan, we found no evidence of spatial or temporal genetic population structure within the Salish Sea and moderate levels of neutral genetic diversity. Multiple paternity in two litters confirmed polyandrous mating, a strategy that may enhance genetic diversity. Relatedness analyses revealed philopatry, with close relatives identified across disparate years, demonstrating that mature females or their relatives return to this nursery ground over time for pupping. These findings provide new insights into the life history of the sixgill shark and emphasize the critical role of nursery habitats, such as the Salish Sea, in their reproductive success, underscoring the need for targeted conservation efforts to protect these sharks and their known critical habitats.

Health benefits of parks are more strongly associated with driving access than walking access in the contiguous United States - Mark R. Kreider; William L. Rice; Cindy S. Leary; Erin O. Semmens; R. Travis Belote; Andrew J. Larson (Landscape and Urban Planning, 2026)

Tree growth response to growing season frost and drought is shaped by species traits and competition in temperate-boreal transition zone forests - Josh Beisel; Colin T. Maher; Justin S. Crotteau; Andrew J. Larson (Forest Ecology and Management, 2026)

Inventory Measurement Rates Lag in Wilderness Areas Across the Western USA - David L. R. Affleck; George C. Gaines; Cici Conroy; Gianna Santino; Andrew J. Larson (Forest Science, 2026)

Morphological and physiological response of conifer seedlings to drought conditioning - Anna C. Ross; Jeremiah R. Pinto; Justin S. Crotteau; Alex Goke; Cara R. Nelson; David L. R. Affleck; Andrew J. Larson (New Forests, 2025)

Significant mortality of old trees across a dry forest landscape, Oregon, USA - James D. Johnston; Paige N. Stephens; Micah R. Schmidt; Sean M.A. Jeronimo; Amanda E. Brackett; Amarina E. Wuenschel; Danielle E.M. Ulrich; Riley H. Paine; Lou F. Duloisy; Skye M. Greenler; Andrew J. Larson; Derek J. Churchill (Forest Ecology and Management, 2025)

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

Caribbean Creep meets Chesapeake Creep: marine bioinvasions and community shifts along the Mid-Atlantic Coast, USA - Amy E. Fowler; April M. H. Blakeslee; Andrew Davinack; Robert Aguilar; Miranda Andersen; Clara Benadon; Henry H. C. Choong; Lindsay Green-Gavrielidis; Sarah R. Greenberg; El Hartshorn; Niels-Viggo Hobbs; Sara Labbe; et al. (Biological Invasions, 2025)
The Mid-Atlantic waters of North America are warming faster than > 90% of other global oceans, leading to significant increases in bottom water temperatures and influencing shifts in marine community structure. Given this modern-day scenario of significant community shifts over space and time, baseline surveys of species diversity are increasingly valuable. Therefore, we performed the first-ever marine bioinvasions Rapid Assessment Survey (RAS) along the Mid-Atlantic waters of the United States in June 2023, focused on marina floating pontoons in Virginia, Maryland, Delaware, and New Jersey. We recorded 29 non-indigenous, 16 cryptogenic, and 10 species that have expanded their ranges in the mid-Atlantic. Seven of these 10 species have expanded northwards from southern locations in the Caribbean (“Caribbean Creep”) or the western Atlantic (“Chesapeake Creep”), and three have expanded southwards. Five non-indigenous species (NIS) were found at more than 60% of the 10 sampled sites: the bryozoans Bugula neritina , Schizoporella pungens , Tricellaria inopinata, macroalgae Codium fragile subsp. fragile , and the sea anemone Aiptasiogeton eruptaurantia . We did not document any new nonindigenous species not already recorded on the Western Atlantic coast. All 10 communities were distinctly different, and species dominance varied by latitude and by site. This first-ever RAS of the Mid-Atlantic waters of the United States provides critical insight into how marine communities have been and are changing as a result of colonization by NIS, including those that have expanded their ranges as a result of human-induced climate change.

The Pragmatic Sceptic: A Practical Approach for Integrating Environmental DNA Into Marine Stock Assessment and Fisheries Management - Diana S. Baetscher; Kristen L. Omori; Daniel R. Goethel; Andrew Olaf Shelton; Aaron M. Berger; Kimberly J. Ledger; Krista M. Nichols; Wesley A. Larson (Fish and Fisheries, 2025)
The ‘omics revolution’ has advanced scientific understanding of marine ecosystems and led to a rapid increase in data that can inform species' population structure, distribution, and abundance. Of the 'omics data types, environmental DNA (eDNA) may present the most cost‐effective opportunity for developing quantitative estimates of abundance trends, a key input for stock assessment models. However, eDNA has yet to be widely adopted for stock status determinations within regional fisheries management organisations. We review progress towards addressing key challenges that limited the application of eDNA in marine fisheries management, including advances in (1) the quantitative relationship between eDNA observations and species biomass, (2) reducing false‐negative and false‐positive detections, (3) defining the spatial scale of eDNA, (4) collecting biological data from eDNA surveys, (5) quantifying uncertainty in eDNA surveys, and (6) responding to scepticism of new survey methods. We use a case study with Pacific hake ( Merluccius productus ) to demonstrate the development of an eDNA index and its direct integration into an age‐structured stock assessment model. Given the many ways in which the field of eDNA has matured, we propose that eDNA can meaningfully inform a range of fisheries management needs, and outline a roadmap for using eDNA in stock assessment models in data‐limited to data‐rich species. A primary impediment to operationalising eDNA as stock assessment model inputs is the lack of interdisciplinary research teams, including geneticists, ecological modellers, and stock assessment scientists, which are necessary to interpret methods and results across scientific disciplines and ensure data are used appropriately.

Pilot Trial of Nutri, a Digital Intervention for Personalized Dietary Management of Diabetes in Safety-Net Primary Care - Marissa Burgermaster; Madalyn Rosenthal; Brandon S. Altillo; Mariana Rendon Flores; Eesha Nayak; Dagny N. Larson; James Custer; Lola Okunade; William M. Tierney; Steven Andrews; Grant Daniels; Paul J. Rathouz (Journal of Nutrition Education and Behavior, 2025)

Herbicides Have Minimal and Variable Effects on the Structure and Function of Bacterial Communities in Agricultural Soils - Margaret Gaylord; Abigail Thompson; Franck E. Dayan; Andrew R. Kniss; Dave Reichert; Kristen Otto; Rebecca Larson; Pankaj Trivedi (Environmental Microbiology, 2025)
Synthetic herbicides are relied on for weed management in the United States, and non‐chemical alternatives, such as tillage, can be inefficient and expensive at an agricultural scale. Previous research examining the influence of weed management strategies on soil microbial communities has shown variability and inconsistency in experimental design and results. This study investigates the impact of repeated applications of glyphosate, a mixture of selective herbicides, and tillage on soil bacterial communities in sugar beet production across two locations in the United States. Using next‐generation sequencing and various assays, we explore the effects on bacterial community structure, composition, and function related to nutrient cycling and soil health. Although transient and minor differences in bacterial community structure could be observed for herbicides and tillage, these statistical differences do not appear to be biologically relevant as the soil function was equivalent for all applied treatments. Our findings provide evidence that repeated herbicide usage does not directly impact soil health and function in sugar beet production. This study emphasises the need for well‐replicated, field‐realistic, and long‐term experiments to understand the ecological consequences of herbicides and tillage in agroecosystems.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Climate‐Induced Physiological Stress Drives Rainforest Mammal Population Declines - Alejandro de la Fuente; Natalie J. Briscoe; Michael R. Kearney; Stephen E. Williams; Kara N. Youngentob; Karen J. Marsh; Lucas A. Cernusak; Lily Leahy; Johan Larson; Andrew K. Krockenberger (Global Change Biology, 2025)
Climate change is a major driver of global biodiversity loss, yet the precise mechanisms linking climate change to population declines remain poorly understood. We developed a novel, broadly applicable framework that integrates biophysical, nutritional, and population modeling to capture fundamental physiological constraints on mammalian herbivores and applied it to investigate the causes of declines in ringtail possums of the Australian Wet Tropics ( Pseudochirops archeri and Hemibelideus lemuroides ). Our approach bridges the gap between mechanistic (“bottom‐up”) models, which simulate species' responses based solely on their traits and local microclimates, and the more common (“top‐down”) statistical models, which infer species' responses from occurrence or abundance data and standard environmental variables. We quantified population dynamics over a 30‐year period by generating species‐specific estimates of temperature and water stress, foraging limitations, and linking these with annual monitoring and nutritional quality within an open population model. Our findings demonstrate that climate change has impacted populations through physiological stress, but in a species‐specific manner. Both species have experienced population collapses at lower elevations and in low‐nutritional sites. For P. archeri , we found evidence that population changes were driven by reduced survival due to overheating and dehydration, alongside diminished recruitment from limited foraging. In contrast, our model suggests that H. lemuroides populations were primarily affected by foraging constraints, emphasizing the importance of considering climate‐driven limitations on foraging activity in addition to direct physiological stress. These mechanistic insights offer a foundation for targeted conservation strategies to mitigate the impacts of climate pressures on wild populations.

All the light we cannot see: Climate manipulations leave short and long‐term imprints in spectral reflectance of trees - Artur Stefanski; Ethan E. Butler; Laura J. Williams; Raimundo Bermudez; J. Antonio Guzmán Q.; Andrew Larson; Philip A. Townsend; Rebecca Montgomery; Jeannine Cavender‐Bares; Peter B. Reich (Ecology, 2025)
Anthropogenic climate change, particularly changes in temperature and precipitation, affects plants in multiple ways. Because plants respond dynamically to stress and acclimate to changes in growing conditions, diagnosing quantitative plant‐environment relationships is a major challenge. One approach to this problem is to quantify leaf responses using spectral reflectance, which provides rapid, inexpensive, and nondestructive measurements that capture a wealth of information about genotype as well as phenotypic responses to the environment. However, it is unclear how warming and drought affect spectra. To address this gap, we used an open‐air field experiment that manipulates temperature and rainfall in 36 plots at two sites in the boreal‐temperate ecotone of northern Minnesota, USA. We collected leaf spectral reflectance (400–2400 nm) at the peak of the growing season for three consecutive years on juveniles (two to six years old) of five tree species planted within the experiment. We hypothesized that these mid‐season measurements of spectral reflectance capture a snapshot of the leaf phenotype encompassing a suite of physiological, structural, and biochemical responses to both long‐ and short‐time scale environmental conditions. We show that the imprint of environmental conditions experienced by plants hours to weeks before spectral measurements is linked to regions in the spectrum associated with stress, namely the water absorption regions of the near‐infrared and short‐wave infrared. In contrast, the environmental conditions plants experience during leaf development leave lasting imprints on the spectral profiles of leaves, attributable to leaf structure and chemistry (e.g., pigment content and associated ratios). Our analyses show that after accounting for baseline species spectral differences, spectral responses to the environment do not differ among the species. This suggests that building a general framework for understanding forest responses to climate change through spectral metrics may be possible, likely having broader implications if the common responses among species detected here represent a widespread phenomenon. Consequently, these results demonstrate that examining the entire spectrum of leaf reflectance for environmental imprints in contrast to single features (e.g., indices and traits) improves inferences about plant‐environment relationships, which is particularly important in times of unprecedented climate change.

Small-scale fire refugia increase soil bacterial and fungal richness and increase community cohesion nine years after fire - Joseph D. Birch; James A. Lutz; Matthew B. Dickinson; James Franklin; Andrew J. Larson; Mark E. Swanson; Jessica R. Miesel (Science of The Total Environment, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Patterns in tree squirrel co-occurrence vary with responses to local land cover in US cities - Rachel N. Larson; Heather A. Sander; Mason Fidino; Julia L. Angstmann; Sheryl Hayes Hursh; Seth B. Magle; Katrina Moore; Carmen M. Salsbury; Theodore Stankowich; Katherine Tombs; Lauren Barczak; Alyssa M. Davidge; et al. (Urban Ecosystems, 2024)

Western larch regeneration more sensitive to wildfire-related factors than seasonal climate variability - Spencer T. Vieira; Kimberley T. Davis; Zachary A. Holden; Andrew J. Larson; Philip E. Higuera (Forest Ecology and Management, 2024)

Fish Invasion of Prairie Pothole Wetlands Reduces Amphipod Abundance, A Key Vertebrate Forage - Jake D. Carleen; Danelle M. Larson; Michael J. Anteau; Megan J. Fitzpatrick; Andrew W. Hafs; Carl W. Isaacson; Breanna R. Keith (Wetlands, 2024)

Review of per- and poly-fluoroalkyl treatment in combustion-based thermal waste systems in the United States - Keith Weitz; Debra Kantner; Andrew Kessler; Haley Key; Judd Larson; Wanda Bodnar; Sameer Parvathikar; Lynn Davis; Nicole Robey; Philip Taylor; Florentino De la Cruz; Thabet Tolaymat; et al. (Science of The Total Environment, 2024)

Discussion: Prioritize perennial grain development for sustainable food production and environmental benefits - Lee R. DeHaan; James A. Anderson; Prabin Bajgain; Andrea Basche; Douglas J. Cattani; Jared Crain; Timothy E. Crews; Christophe David; Olivier Duchene; Jessica Gutknecht; Richard C. Hayes; Fengyi Hu; et al. (Science of The Total Environment, 2023)

Mesic mixed-conifer forests are resilient to both historical high-severity fire and contemporary reburns in the US Northern Rocky Mountains - Melissa R. Jaffe; Mark R. Kreider; David L.R. Affleck; Philip E. Higuera; Carl A. Seielstad; Sean A. Parks; Andrew J. Larson (Forest Ecology and Management, 2023)

Acrylic acid and DMSP lyases in the green algae Ulva - Giovanna Pesante; Edith Forestier; Swen Langer; Andrew Danby; John Angus; Mark Gronnow; Joseph P. Bennett; Tony R. Larson; Thierry Tonon (Algal Research, 2023)

Gene flow influences the genomic architecture of local adaptation in six riverine fish species - Yue Shi; Kristen L. Bouska; Garrett J. McKinney; William Dokai; Andrew Bartels; Megan V. McPhee; Wesley A. Larson (Molecular Ecology, 2023)
Understanding how gene flow influences adaptive divergence is important for predicting adaptive responses. Theoretical studies suggest that when gene flow is high, clustering of adaptive genes in fewer genomic regions would protect adaptive alleles from recombination and thus be selected for, but few studies have tested it with empirical data. Here, we used restriction site‐associated sequencing to generate genomic data for six fish species with contrasting life histories from six reaches of the Upper Mississippi River System, USA. We used four differentiation‐based outlier tests and three genotype–environment association analyses to define neutral single nucleotide polymorphisms (SNPs) and outlier SNPs that were putatively under selection. We then examined the distribution of outlier SNPs along the genome and investigated whether these SNPs were found in genomic islands of differentiation and inversions. We found that gene flow varied among species, and outlier SNPs were clustered more tightly in species with higher gene flow. The two species with the highest overall F ST (0.0303–0.0720) and therefore lowest gene flow showed little evidence of clusters of outlier SNPs, with outlier SNPs in these species spreading uniformly across the genome. In contrast, nearly all outlier SNPs in the species with the lowest F ST (0.0003) were found in a single large putative inversion. Two other species with intermediate gene flow ( F ST ~ 0.0025–0.0050) also showed clustered genomic architectures, with most islands of differentiation clustered on a few chromosomes. Our results provide important empirical evidence to support the hypothesis that increasingly clustered architecture of local adaptation is associated with high gene flow.

Differences in fouling community composition and space occupation across broad spatial and temporal scales - Elizabeth B. Jewett; Katherine N. Lawson; Kristen J. Larson; Brianna M. Tracy; Safra Altman; Andrew L. Chang; Scott Cowan; Jeffrey A. Crooks; Tamar Huber; Elizabeth H. Wells; Gregory M. Ruiz (Frontiers in Marine Science, 2022)
Sessile marine invertebrate (biofouling) communities have served as an important model in ecology for evaluating fundamental patterns and processes, including invasion dynamics, which vary at broad spatial and temporal scales. Here, we tested for differences in biofouling community development among three biogeographically distinct bays in North America (Chesapeake Bay, Tampa Bay, and San Francisco Bay), exploring possible explanations for differential non-native species success. In particular, we aimed to examine if San Francisco Bay (a global hotspot for non-native species richness) differed in composition and space occupation, especially since open space can facilitate colonization. Additionally, we explored how biogeography, assembly and succession dynamics over the short and long term, and space availability affect marine communities across broad spatial scales. Patterns of community assembly differed among bays, with more bare space and less secondary cover (species settling on species) in San Francisco Bay. San Francisco Bay was also distinguished by a higher percent cover of Tunicata (almost all of which are non-native and historically absent) over multiple time scales. Cirripedia recruited on bare panels in all three Bays but cover increased only in Tampa Bay, as soak time increased. Tube-dwelling Polychaeta distinguished Chesapeake Bay from Tampa Bay and San Francisco Bay. Low-salinity events temporarily restructured the communities in all three bays. Whether differences among bays reflect coastal versus bay-specific patterns remains to be tested.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Comparison of the distribution and phenology of Arctic Mountain plants between the early 20th and 21st centuries - Andrew S. MacDougall; Paul Caplat; Johan Olofsson; Matthias B. Siewert; Colin Bonner; Ellen Esch; Malie Lessard‐Therrien; Hannah Rosenzweig; Anne‐Kathrin Schäfer; Pia Raker; Hassan Ridha; Kjell Bolmgren; et al. (Global Change Biology, 2021)
Arctic plants are adapted to climatic variability, but their long‐term responses to warming remain unclear. Responses may occur by range shifts, phenological adjustments in growth and reproduction, or both. Here, we compare distribution and phenology of 83 arctic and boreal mountain species, sampled identically in the early 20th (1917–1919) and 21st centuries (2017–2018) from a region of northern Sweden that has warmed significantly. We test two compensatory hypotheses to high‐latitude warming—upward shifts in distribution, and earlier or extended growth and reproduction. For distribution, we show dramatic upward migration by 69% of species, averaging 6.1 m per decade, especially boreal woodland taxa whose upward expansion has reduced arctic montane habitat by 30%. Twenty percent of summit species showed distributional shifts but downward, especially moisture‐associated snowbed flora. For phenology, we detected wide inter‐annual variability in the onset of leafing and flowering in both eras. However, there was no detectable change in growing‐season length, relating to two mechanisms. First, plot‐level snow melt data starting in 1917 demonstrated that melt date, rather than vernal temperatures, better predicts plant emergence, with snow melt influenced by warmer years having greater snowfall—warmer springs did not always result in earlier emergence because snowbeds can persist longer. Second, the onset of reproductive senescence between eras was similar, even when plant emergence was earlier by a month, possibly due to intensified summer heat stress or hard‐wired ‘canalization’ where senescence occurs regardless of summer temperature. Migrations in this system have possibly buffered arctic species against displacement by boreal expansion and warming, but ongoing temperature increases, woody plant invasion, and a potential lack of flexibility in timing of senescence may foreshadow challenges.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Evaluating Restoration Treatment Effectiveness through a Comparison of Residual Composition, Structure, and Spatial Pattern with Historical Reference Sites - Miles E LeFevre; Derek J Churchill; Andrew J Larson; Sean M A Jeronimo; Jamie Bass; Jerry F Franklin; Van R Kane (Forest Science, 2020)
Forest-restoration efforts are increasing in the western United States in response to realized and expected changes in climate and disturbance regimes. Managers are challenged to find practical and defensible targets to shift forest composition, structure, and spatial pattern to a more resistant and resilient state. The Northeast Washington Forest Vision 2020 project on the Colville National Forest presented an opportunity to map and use previously uncaptured mesic stand-level historical reference conditions to a large restoration project. We reconstructed historical forest conditions in 12 plots across a range of plant-association groups and mapped five restoration treatment units after implementation. We evaluated treatment effectiveness both in terms of meeting the prescriptions’ stated objectives and by similarity to observed reference conditions using metrics of density, species composition, clump-size patterns, and open-space patterns. We found that dry plant associations were historically dominated by distributed clumps of large shade-intolerant trees, whereas cold mesic plant associations were structured as a gap-matrix spatial pattern. Treatments were effective at meeting prescribed density and species-composition targets, but generally resulted in stands that were overly uniform or clumped compared to historical reference conditions.

Caveolin-1 regulates medium spiny neuron structural and functional plasticity - Katherine R. Tonn Eisinger; Andrew D. Chapp; Samuel P. Swanson; Daniel Tam; Natalie M. Lopresti; Erin B. Larson; Mark J. Thomas; Lorene M. Lanier; Paul G. Mermelstein (Psychopharmacology, 2020)

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Fixing a snag in carbon emissions estimates from wildfires - Jeffrey E. Stenzel; Kristina J. Bartowitz; Melannie D. Hartman; James A. Lutz; Crystal A. Kolden; Alistair M. S. Smith; Beverly E. Law; Mark E. Swanson; Andrew J. Larson; William J. Parton; Tara W. Hudiburg (Global Change Biology, 2019)
Wildfire is an essential earth‐system process, impacting ecosystem processes and the carbon cycle. Forest fires are becoming more frequent and severe, yet gaps exist in the modeling of fire on vegetation and carbon dynamics. Strategies for reducing carbon dioxide (CO 2 ) emissions from wildfires include increasing tree harvest, largely based on the public assumption that fires burn live forests to the ground, despite observations indicating that less than 5% of mature tree biomass is actually consumed. This misconception is also reflected though excessive combustion of live trees in models. Here, we show that regional emissions estimates using widely implemented combustion coefficients are 59%–83% higher than emissions based on field observations. Using unique field datasets from before and after wildfires and an improved ecosystem model, we provide strong evidence that these large overestimates can be reduced by using realistic biomass combustion factors and by accurately quantifying biomass in standing dead trees that decompose over decades to centuries after fire (“snags”). Most model development focuses on area burned; our results reveal that accurately representing combustion is also essential for quantifying fire impacts on ecosystems. Using our improvements, we find that western US forest fires have emitted 851 ± 228 Tg CO 2 (~half of alternative estimates) over the last 17 years, which is minor compared to 16,200 Tg CO 2 from fossil fuels across the region.

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wildfire in the American West - Andrew J. Larson (Ecology, 2018)

A Large-Scale, Multiagency Approach to Defining a Reference Network for Pacific Northwest Streams - Stephanie Miller; Peter Eldred; Ariel Muldoon; Kara Anlauf-Dunn; Charlie Stein; Shannon Hubler; Lesley Merrick; Nick Haxton; Chad Larson; Andrew Rehn; Peter Ode; Jake Vander Laan (Environmental Management, 2016)

Spatial aspects of tree mortality strongly differ between young and old‐growth forests - Andrew J. Larson; James A. Lutz; Daniel C. Donato; James A. Freund; Mark E. Swanson; Janneke HilleRisLambers; Douglas G. Sprugel; Jerry F. Franklin (Ecology, 2015)
Rates and spatial patterns of tree mortality are predicted to change during forest structural development. In young forests, mortality should be primarily density dependent due to competition for light, leading to an increasingly spatially uniform pattern of surviving trees. In contrast, mortality in old‐growth forests should be primarily caused by contagious and spatially autocorrelated agents (e.g., insects, wind), causing spatial aggregation of surviving trees to increase through time. We tested these predictions by contrasting a three‐decade record of tree mortality from replicated mapped permanent plots located in young ( 300‐year‐old) Abies amabilis forests. Trees in young forests died at a rate of 4.42% per year, whereas trees in old‐growth forests died at 0.60% per year. Tree mortality in young forests was significantly aggregated, strongly density dependent, and caused live tree patterns to become more uniform through time. Mortality in old‐growth forests was spatially aggregated, but was density independent and did not change the spatial pattern of surviving trees. These results extend current theory by demonstrating that density‐dependent competitive mortality leading to increasingly uniform tree spacing in young forests ultimately transitions late in succession to a more diverse tree mortality regime that maintains spatial heterogeneity through time.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Spatially nonrandom tree mortality and ingrowth maintain equilibrium pattern in an old‐growth Pseudotsuga–Tsuga forest - James A. Lutz; Andrew J. Larson; Tucker J. Furniss; Daniel C. Donato; James A. Freund; Mark E. Swanson; Kenneth J. Bible; Jiquan Chen; Jerry F. Franklin (Ecology, 2014)
Mortality processes in old‐growth forests are generally assumed to be driven by gap‐scale disturbance, with only a limited role ascribed to density‐dependent mortality, but these assumptions are rarely tested with data sets incorporating repeated measurements. Using a 12‐ha spatially explicit plot censused 13 years apart in an approximately 500‐year‐old Pseudotsuga – Tsuga forest, we demonstrate significant density‐dependent mortality and spatially aggregated tree recruitment. However, the combined effect of these strongly nonrandom demographic processes was to maintain tree patterns in a state of dynamic equilibrium. Density‐dependent mortality was most pronounced for the dominant late‐successional species, Tsuga heterophylla . The long‐lived, early‐seral Pseudotsuga menziesii experienced an annual stem mortality rate of 0.84% and no new recruitment. Late‐seral species Tsuga and Abies amabilis had nearly balanced demographic rates of ingrowth and mortality. The 2.34% mortality rate for Taxus brevifolia was higher than expected, notably less than ingrowth, and strongly affected by proximity to Tsuga . Large‐diameter Tsuga structured both the regenerating conspecific and heterospecific cohorts with recruitment of Tsuga and Abies unlikely in neighborhoods crowded with large‐diameter competitors ( P

Making Monitoring Count: Project Design for Active Adaptive Management - Andrew J. Larson; R. Travis Belote; Matthew A. Williamson; Gregory H. Aplet (Journal of Forestry, 2013)

Genetic variants associated with the white blood cell count in 13,923 subjects in the eMERGE Network - David R. Crosslin; Andrew McDavid; Noah Weston; Sarah C. Nelson; Xiuwen Zheng; Eugene Hart; Mariza de Andrade; Iftikhar J. Kullo; Catherine A. McCarty; Kimberly F. Doheny; Elizabeth Pugh; Abel Kho; et al. (Human Genetics, 2012)

Relatedness and polyandry of sixgill sharks, Hexanchus griseus, in an urban estuary - Shawn Larson; Jeff Christiansen; Denise Griffing; Jimiane Ashe; Dayv Lowry; Kelly Andrews (Conservation Genetics, 2011)

Cryptic gametic interactions confer both conspecific and heterospecific advantages in the Chrysochus (Coleoptera: Chrysomelidae) hybrid zone - Merrill A. Peterson; Erica L. Larson; Margaret Brassil; Kati J. Buckingham; Danielle Juárez; Joseph Deas; Donna Mangloña; Michael A. White; Jonathan Maslan; Andrew Schweitzer; Kirsten J. Monsen (Genetica, 2011)

Age, muscle fatigue, and walking endurance in pre-menopausal women - Gary R. Hunter; C. Scott Bickel; Pedro Del Corral; Nuala M. Byrne; Andrew P. Hills; D. Enette Larson-Meyer; Marcas M. Bamman; Bradley R. Newcomer (European Journal of Applied Physiology, 2011)

Extraction of the magnetohydrodynamic blood flow potential from the surface electrocardiogram in magnetic resonance imaging - Grace M. Nijm; Steven Swiryn; Andrew C. Larson; Alan V. Sahakian (Medical & Biological Engineering & Computing, 2008)